2016
DOI: 10.1038/hr.2016.169
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Cardiac structural remodeling in hypertensive cardiomyopathy

Abstract: Heart failure with preserved ejection fraction (HFpEF), which is a primary driver of morbidity and mortality, accounts for approximately half of all heart failure cases. Therefore, it is essential to develop preclinical animal models for HFpEF pharmacological treatment strategies. We created a porcine model of severe hypertension and hyperlipidemia by using a combination of deoxycorticosterone acetate (DOCA, 100 mg kg), Western diet (WD) and angiotensin II infusion. Systolic blood pressure, echocardiography an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The authors are retracting this article [1]. In their recent work the authors have found that the degree of fibrosis in the different walls of the left atrium in pigs with hypertensive cardiomyopathy is the same.…”
mentioning
confidence: 99%
“…The authors are retracting this article [1]. In their recent work the authors have found that the degree of fibrosis in the different walls of the left atrium in pigs with hypertensive cardiomyopathy is the same.…”
mentioning
confidence: 99%